Extracellular Vesicles in Infrapatellar Fat Pad from Osteoarthritis Patients Impair Cartilage Metabolism and Induce Senescence - Yumei Cao; Jianzhao Ruan; Jingliang Kang; Xiaoyu Nie; Weiren Lan; Guangfeng Ruan; Jia Li; Zhaohua Zhu; Weiyu Han; Su'an Tang; Changhai Ding (Advanced Science, 2024)
Abstract Infrapatellar fat pad (IPFP) is closely associated with the development and progression of knee osteoarthritis (OA), but the underlying mechanism remains unclear. Here, it is find that IPFP from OA patients can secret small extracellular vesicles (sEVs) and deliver them into articular chondrocytes. Inhibition the release of endogenous osteoarthritic IPFP‐sEVs by GW4869 significantly alleviated IPFP‐sEVs‐induced cartilage destruction. Functional assays in vitro demonstrated that IPFP‐sEVs significantly promoted chondrocyte extracellular matrix (ECM) catabolism and induced cellular senescence. It is further demonstrated that IPFP‐sEVs induced ECM degradation in human and mice cartilage explants and aggravated the progression of experimental OA in mice. Mechanistically, highly enriched let‐7b‐5p and let‐7c‐5p in IPFP‐sEVs are essential to mediate detrimental effects by directly decreasing senescence negative regulator, lamin B receptor (LBR). Notably, intra‐articular injection of antagomirs inhibiting let‐7b‐5p and let‐7c‐5p in mice increased LBR expression, suppressed chondrocyte senescence and ameliorated the progression of experimental OA model. This study uncovers the function and mechanism of the IPFP‐sEVs in the progression of OA. Targeting IPFP‐sEVs cargoes of let‐7b‐5p and let‐7c‐5p can provide a potential strategy for OA therapy.